Analisis Kinerja Baznas Kabupaten Sukoharjo Dengan Metode Balanced Scorecard - Denta Nirmarum; Mansur Efendi (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
The optimization of zakat management requires strong institutional support. One effort to achieve this is by evaluating the performance of zakat management institutions, particularly the National Amil Zakat Agency (BAZNAS). Several performance measurement models have been developed, such as IZN, IDZ, CIBEST, IMZ, ISZM, and the Balanced Scorecard. These models enable a comprehensive and simultaneous performance evaluation of BAZNAS. For example, a previous study analyzed the performance of BAZNAS Sukoharjo using the IZN model, with results indicating a "fair" performance. To build on this research, the present study uses field research with a descriptive qualitative approach, employing the Balanced Scorecard analysis. It measures performance from four perspectives: financial, customer (muzakki), internal business processes, and learning and growth. The results show that the performance of BAZNAS Sukoharjo, evaluated using the Balanced Scorecard, is rated "good" in the financial (zakat fund growth), customer (muzakki), and internal business process (programs implemented) perspectives, with a score of "1." Furthermore, the learning and growth perspective also achieved a "good" rating, with a score of "1." These results indicate that the performance has met the work targets, as well as the institution's vision and mission.